The protective effects of L‐carnitine on myocardial ischaemia–reperfusion injury in patients with rheumatic valvular heart disease undergoing CPB surgery are associated with the suppression of NF‐κB pathway and the activation of Nrf2 pathway. (26th August 2019) - Li, Ming; Xu, Suochun; Geng, Yan; Sun, Lei; Wang, Ruili; Yan, Yang; Wang, Haichen; Li, Yongxin; Yi, Qiuyue; Zhang, Yongjian; Hao, Junjun; Deng, Chao; et al.
Abstract: Myocardial ischaemia–reperfusion injury (MIRI) is a main pathophysiologic change following CPB surgery. L‐carnitine, a natural amino acid, is able to transport fatty acids for generating energy and has a protective effect on MIRI. We aim to investigate the protective effect of L‐carnitine on MIRI in patients with rheumatic valvular heart disease (RVHD) performed CPB surgical operation and the underlying mechanism. In this study, patients were randomized to three groups. L‐carnitine was added to the crystalloid cardioplegic solution for experimental group 1 (6 g/L) and experimental group 2 (12 g/L), whereas no L‐carnitine was used in the control group. Our results showed that L‐carnitine significantly attenuated myocardial injury after surgery in these patients. L‐carnitine decreased serum markers of myocardial injury including CK‐MB, cTnI, hs‐cTnT and IMA. L‐carnitine increased left ventricular ejection fraction (LVEF) but reduced wall motion score index (WMSI) after operation. L‐carnitine also inhibited myeloperoxidase (MPO) activity and inflammatory cytokines in the myocardium of patients after unclamping the aorta. Additionally, L‐carnitine increased levels of superoxide dismutase (SOD) and catalase (CAT) while decreased levels of malondialdehyde (MDA) and protein carbonyl content in the myocardium of patients after unclamping the aorta. Moreover, L‐carnitine suppressed the activation of nuclear factor kappa B (NF‐κB) and activated nuclear factor erythroid 2‐related factor 2 (Nrf2). There was also no significant difference in these indices between two experimental groups after unclamping the aorta. Taken together, L‐carnitine had a protective effect against CPB‐induced MIRI in patients with RVHD, which might be related to its modulation of NF‐κB and Nrf2 activities.